2011
DOI: 10.2214/ajr.10.4877
|View full text |Cite
|
Sign up to set email alerts
|

MRI Characteristics of the Uterine Junctional Zone: From Normal to the Diagnosis of Adenomyosis

Abstract: Adenomyosis can be diagnosed using MRI with a diagnostic accuracy of 85%. The most important MR finding in making the diagnosis is thickness of the junctional zone exceeding 12 mm. The principal limitation of MRI is the absence of a definable junctional zone on imaging, which occurs in 20% of premenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
123
3
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(141 citation statements)
references
References 46 publications
5
123
3
10
Order By: Relevance
“…This limitation appears to be in line with previous studies reporting that the junctional zone cannot be delineated in about 30-50 % postmenopausal women (Bazot et al, 2001;Novellas et al;He et al). To assess junctional zone, while many studies measured the ratio of junctional zone thickness, whether in healthy women or women diagnosed with adenomyosis, no previous study reported the ratio of junctional zone volume (Meylaerts et al).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This limitation appears to be in line with previous studies reporting that the junctional zone cannot be delineated in about 30-50 % postmenopausal women (Bazot et al, 2001;Novellas et al;He et al). To assess junctional zone, while many studies measured the ratio of junctional zone thickness, whether in healthy women or women diagnosed with adenomyosis, no previous study reported the ratio of junctional zone volume (Meylaerts et al).…”
Section: Discussionsupporting
confidence: 76%
“…The simplest and widely used measure is the thickness of the endometrium and the junctional zone for the morphological analysis of uterus on the medical images. In general, while the thickness of junctional zone is over 12 mm in adenomyosis, the thickness of less than 10 mm for endometrium is accepted normal in reproductive age women (Novellas et al, 2011;Sofic et al, 2016). Nevertheless, the thickness measurement is performed on the any point on both the anterior or posterior uterine wall and there is no standard measuring point on the uterine wall (Kido et al, 2007;Exacoustos et al, 2011;He et al;Meylaerts et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Mainly because of the difference in cell origin, the outer myometrium presents little or no dependence on hormonal stimulation, while cyclical variation of the junctional zone thickness is similar to that of the endometrium [33]. We therefore conclude that the observed stiffness variation of the myometrium (Fig.…”
Section: Discussionmentioning
confidence: 55%
“…Obscuration of the JZ has been reported as a postmenopausal change resulting from progressive dehydration and fibrous involution of the outer myometrium. 10 This might also explain the reduced recognition of the JZ in our study; the JZ remained visible in 12 of 16 premenopausal patients after chemotherapy, although the hormonal status was similar to that of a postmenopausal state. The differences in visualization of the JZ between postmenopausal women previously reported and post-chemotherapy premenopausal patients described in our study might be due to differences in the degree and duration of low hormonal levels.…”
Section: Discussionmentioning
confidence: 60%
“…1,[9][10][11][12][13][14][15] The changes observed in the MR appearance of ovaries in premenopausal patients, (i.e., decreased volume of the ovaries, intensity of ovarian tissues on T 2 -WI, and visualization of the follicles), could be explained by the ovarian toxicity induced by NACT. This toxicity might be primarily caused by the platinum-based compound.…”
Section: Discussionmentioning
confidence: 99%